(untitled) (Journal of Computational Mathematics, 1999)
In the theoretical study of numerical solution of stiff ODEs, it usually assumes that the right-hand function f(y) satisfy one-side Lipschitz condition ≤ v' ||y-z||^2,f: Ω C^m → C^m, or another related one-side Lipschitz condition [F(Y)-F(Z),Y-Z]_D ≤ v'' ||Y-Z||^2_D, F:Ω^s C^ms → C^ms, this paper demonstrates that the difference of the two sets of all functions satisfying the above two conditions respectively is at most that v'-v'' only is constant independent of stiffness of function f.